Financial Status and Recurrence of Modifiable Gamble Variables of non-Transferable Sicknesses in Youthful Grown-ups (age 25-40 years) of Bahawalpur - Summaira Hassan, Sundas Hamna (Pakistan Journal of Medical & Health Sciences, 2023)
Aims: To find out the frequency of modifiable gamble variables of non-transferable sicknesses in youthful grown-ups (age 25-40 yrs) of Bahawalpur and to compare modifiable gamble variables of non-transferable sicknesses among different financial status. Study Design: Descriptive cross sectional study Place and Duration: Four areas of Bahawalpur City: Model Town A &B, Tibba Badar Sher and Bhatta No. 2,3 from April 2019 to September 2019. Methodology: Multi stage sampling was done to draw the sample. The sample size of 240 was calculated by using WHO software sample size calculation after adding 10% response error. Data was collected through a predesigned and pretested questionnaire. BMI was calculated by measuring height and weight. The data was entered and analyzed through SPSS version 24.Mean and standard deviations were calculated for quantitative variables like age and BMI. Simple Frequencies and percentages were calculated. Chi square test was used as the test of significance for qualitative variables. Results: The frequency of various gamble variables was found highest in the participants falling in the working financial class (58.3%) i.e., smoking (11.3%), low dietary intake of natural products like fruits and vegetables 55.6% and 51.7% respectively while low physical activity 71%. The relationship of these factors with gender and age was statistically significant. Conclusion: Varieties in the dispersion of hazard factors contends specific concentration over individual ways of behaving, individual decisions and obligations to be featured . Purposeful planning of conditions to advance sound ways of behaving is fundamental and promising to diminish the pervasiveness of these ways of life sicknesses. Keywords: Modifiable gamble variables, youthful grown up, sickness